ANAPHYLACTIC SHOCK DUE TO BEE BROOD AND DRONE CONSUMPTION: A RARE CASE - Farah Ibnu Khan; Laurentius Johan Ardian (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Anaphylactic shock is severe manifestation of anaphylactic reaction. Anaphylactic is rapid onset systemic hypersensitivity reaction and potentially life threatening. The trigger factors of anaphylactic is various. One of them is animal venom such as honey bee venom from Hymenoptera order. Anaphylactic due to bee drone brood consumption is rarely reported. In this case, will be presented a 19-year-old male who comes to emergency department with hypotension, tachycardia, angioedema, general urticarial, and high level of leucocyte after an hour consumed bee drone and brood food product. In emergency department, soon after he came, was given epinephrine 0,3 ml intravena, hemodynamics stabilization, and he was treated in hospital. After one day treated, there was no other symptoms and there was improvement of conditions. By the advice of internist, patient was discharged. Food allergy by the honeybee and the product is rarely reported but it can be a life-threatening case. The right and rapid therapy is very needed in this case for giving the best output for the patient. ABSTRAK Syok anafilaksis merupakan suatu manifestasi dari reaksi anafilaksis berat. Anafilaksis sendiri adalah reaksi hipersensitivitas sistemik dengan onset cepat yang dapat menyebabkan kematian. Faktor pemicu anafilaksis beraneka ragam salah satunya adalah racun dari hewan salah satunya adalah lebah madu dari ordo hymenoptera. Kasus anafilaksis akibat konsumsi larva, pupa, dan lebah muda sendiri masih jarang dilaporkan. Pada laporan kasus kali ini akan dipaparkan tentang seorang laki-laki berusia 19 tahun datang ke Instalasi Gawat Darurat dengan hipotensi, takikardia, angioedema, urtikaria generalisata, dan peningkatan leukosit setelah mengonsumsi makanan olahan dari tawon. Saat di Instalasi Gawat Darurat pasien diberikan injeksi epinefrin 0,3 ml secara intravena segera setelah pasien datang dan dilakukan stabilisasi hemodinamik serta rawat inap di Rumah Sakit. Satu hari setelah perawatan tidak ada gejala tambahan dan terdapat perbaikan kondisi, atas advis dokter spesialis penyakit dalam, pasien dipulangkan. Alergi makanan olahan dari tawon memang jarang dilaporkan, namun dapat menjadi kasus yang mengancam nyawa. Tatalaksana yang cepat dan tepat sangat diperlukan pada kasus seperti ini untuk dapat memberikan output yang baik.